Habits of mind across the curriculum : practical and creative strategies for teachers - Costa, Arthur L.; Kallick, Bena (Association for Supervision and Curriculum Development, 2009)
Real-life experiences from K-12 teachers provide readers with insight and model lessons for weaving the development of strong habits of mind into daily instruction in language arts, music, physical education, social studies, math, foreign language, and other content areas.